ROLES AND ACTIVITIES OF FUNGI ASSOCIATED WITH AGARWOOD AND KRITSANA TREE IN THAILAND - Chalermpongse, Aniwat; Siripatanadilok, Somkid; Sangthongprao, Suvit (วารสารวนศาสตร์ไทย, 2022)
Survey and experiments to determine the roles and activities of fungi in the formation of incence aloes-wood or agarwood on Kritsana tree (Aquilaria crassna Pierre ex H. Lec.) were carried out at Khaoyai National Park, Nakhon Ratchasima, and other provinces. Open wounding and controlled infection of fungi were studied. Many fungi infected in the artificial woundings, fungi colonized on naturally kritsana trees, wood-rotting fungi, seed-borne and seedling diseases and mycorrhizal association with kritsana or agarwood threes were isolated and identified. Results revealed that kritsana or agar (oleoresin deposit) formation did not correlate with the roles or activities of specific fungi, as was previously believed, but it was obviously formed by the interaction of the tree host through injuries or woundings which might be derived from the mechanical, physical, chemical or biological processes. However the result of a protective reaction of the tree host to injuries, woundings or biological invasions to form oleoresin deposits in kritsana trees was expected as the main causes, the fungal infection in agarwood would be degraded to the quality and reduced in weight of agar or kritsana.